2010
DOI: 10.1108/03068291011062489
|View full text |Cite
|
Sign up to set email alerts
|

Political participation and life satisfaction: a cross‐European analysis

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
0
26
2
Order By: Relevance
“…Flavin and Keane (2012), who examined the relationship between life satisfaction and political participation using data from the ANES 2000 (American National Election Study), concluded that this link is confined to non-conflictual forms of participation only; no relationship was found as regards engagement in political protest. Pacheco and Lange (2010) in the ESS 2006 data found that only one kind of political participation activity -membership or collaboration with a political partyhas a positive effect on life satisfaction. In our results, not only were the well-being indicators -satisfaction with life as a whole and general happiness -of more politically participative individuals higher, but also satisfaction with different areas of social life (with government, the way democracy works, with the state of the economy and the state of health services).…”
Section: Discussionmentioning
confidence: 99%
“…Flavin and Keane (2012), who examined the relationship between life satisfaction and political participation using data from the ANES 2000 (American National Election Study), concluded that this link is confined to non-conflictual forms of participation only; no relationship was found as regards engagement in political protest. Pacheco and Lange (2010) in the ESS 2006 data found that only one kind of political participation activity -membership or collaboration with a political partyhas a positive effect on life satisfaction. In our results, not only were the well-being indicators -satisfaction with life as a whole and general happiness -of more politically participative individuals higher, but also satisfaction with different areas of social life (with government, the way democracy works, with the state of the economy and the state of health services).…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent research has not only highlighted the role of political regimes and institutions, but almost consequently also shifted attention to satisfaction with democracy in particular. Karp et al (2003), for instance, examine whether EU institutions are considered as legitimate, Pacheco and Lange (2010) investigate the role of political participation. Wagner et al (2009) identify institutional quality as an important input with respect to measures of regime satisfaction, as do Bjørnskov et al (2010).…”
Section: Where We Start Frommentioning
confidence: 99%
“…Controlling for language and religion, the authors found no significant effect of political participation on subjective well‐being. In another study based on data from the 2006/2007 European Social Survey, Pacheco and Lange () found that political participation had a statistically significant, strong, and positive effect on life satisfaction, after dealing with endogeneity problems through a two‐step regression modeling procedure. Similarly, using data from the 18 AmericasBarometer country surveys, Weitz‐Shapiro and Winters () initially found a positive association between voting and life satisfaction in Latin America, albeit that the relationship was attenuated in countries with enforced compulsory voting.…”
Section: Background Literature and Theoretical Frameworkmentioning
confidence: 99%